Evaluation of Putative Association Between Celiac Disease and Helicobacter pylori Infection in Hyderabad, Sindh: Association Between Celiac Disease and Helicobactor pylori Infection (Biological Sciences - PJSIR, 2020)
Celiac disease is an autoimmune mediated enteropathy caused by ingestion of gluten and affects approximately 1% of the population. It has significant deleterious effects on health and mortality. Helicobacter pylori is the major causative agent of peptic ulcer and gastric cancer. The aim of this study was to assess the prevalence of both H. pylori (HP) and celiac disease (CD) as mono and co-infections and to find out the possible association between CD and presence of HP. A total of 172 blood samples from individuals suspected of CD and HP infection were collected during March to December, 2015 from Hyderabad. Serum analyzed for presence of anti-HP antibodies for evaluation of HP infection and tissue transglutaminase IgA antibodies (tTGA) for detection of CD. The serodiagnosis data revealed that out of 172 samples tested 19.19% were positive for CD which included 6.98% (n=12) male patients, whereas 12.21% (n=21) were females. The HP was detected in 44.77% (n=77) including 22.09% (n=38) males and 22.67% (n=39) females out of the 33 CD positive cases, HP was detected in 17 (9.88%). HP in CD positive cases was found to be 6.60% in males 9.43% in females respectively. The HP prevalence in non-CD patients appeared to be high such as 18.02% and 16.86%. In conclusion, the data of the present study indicates that HP is more prevalent than CD.